2022
DOI: 10.2147/dddt.s386805
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritin Protects Against Cardiac Fibrosis After Myocardial Infarction by Inhibiting CCL5 Expression and the NF-κB Signaling Pathway

Abstract: Purpose Despite significant advances in interventional treatment, myocardial infarction (MI) and subsequent cardiac fibrosis remain major causes of high mortality worldwide. Liquiritin (LQ) is a flavonoid extract from licorice that possesses a variety of pharmacological properties. However, to our knowledge, the effects of LQ on myocardial fibrosis after MI have not been reported in detail. The aim of our research was to explore the potential role and mechanism of LQ in MI-induced myocardial damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Thus, it can be concluded that the incidence and duration of AF can be effectively reduced via repressing fibrosis (Boyle et al., 2021; Heijman et al., 2014). In our study, GA reduced myocardial fibrosis area in a concentration‐dependent manner, analogous to the previous report demonstrating the effects of licorice‐related bioactive substances and compounds on attenuating myocardial fibrosis (Gao, Kan, et al., 2022; Han et al., 2022). Moreover, GA has been documented to exert its anti‐inflammatory effects on AF and to effectively inhibit the expressions of inflammatory factors (IL‐4, IL‐6, IL‐13, and IL‐17).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it can be concluded that the incidence and duration of AF can be effectively reduced via repressing fibrosis (Boyle et al., 2021; Heijman et al., 2014). In our study, GA reduced myocardial fibrosis area in a concentration‐dependent manner, analogous to the previous report demonstrating the effects of licorice‐related bioactive substances and compounds on attenuating myocardial fibrosis (Gao, Kan, et al., 2022; Han et al., 2022). Moreover, GA has been documented to exert its anti‐inflammatory effects on AF and to effectively inhibit the expressions of inflammatory factors (IL‐4, IL‐6, IL‐13, and IL‐17).…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, we showed that LQ could suppress the proliferation of keratinocytes induced by TNF‐α in a dose‐dependent manner, which was beneficial to alleviating the hyperplasia of the epidermis. Reports also show that LQ has a good safety record even when used at high concentrations of 80 mg/kg (Han et al, 2022; Mou et al, 2021). This was important in order for us to perform in vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB pathway is a typical proinflammatory signaling pathway, playing a crucial role in the functional outcome after stroke. [30,31] In fact, in vitro studies have found that the Sirt1/NF-κB pathway substantially affects cerebral IS in rat neurons affected by apoptosis. [32] Moreover, research in mice shows that inhibition of the NF-κB/NLRP3 signaling pathway partially reduced stroke-induced white matter damage and alleviated microglial pyroptosis.…”
Section: Discussionmentioning
confidence: 99%